Formulation and Evaluation of Silymarin Microcrystals by In- Situ Micronization Technique - Noor, Ala’a Dheia; B.H. Al-Khedairy, Eman (Iraqi Journal of Pharmaceutical Sciences, 2019)
Silymarin (SM) is a plant extract obtained from Silybum marianum( milk thistle) . It is class II type drug according to Biopharmaceutics Classification System with low bioavailability due to its low solubility. Micro/nanonization during crystallization, surface modification and crystal structure modification may improve the dissolution rate of poorly water-soluble drugs. The aim of this study was to increase the water solubility and dissolution rate of SM by in-situ micronization using solvent change either by stirring or ultrasonic method. Stabilizers like Gelatin, PVP-K30, HPMC15, Pulullan were used to stabilize the prepared ultrafine crystals. Effect of type and concentration of hydrophilic polymer, solvent: antisolvent volume ratio and the effect of ultrasonic irradiation were studied. The prepared microcrystals were evaluated for their %yield, water solubility, crystals structure by XRD,DSC, and SEM. Particle size and dissolution rate were also tested . Silymarin microcrystals prepared by ultrasonic method and stabilized by 0.1%gelatin using 1:2 solvent: anti-solvent volume ratio showed the best results with particle size reduction from mean diameter of 1.5µm (untrated silymarin) to 0.43µm with uniform morphology and enhanced solubility and dissolution.